Health in the Polish People’s Republic - Zatoński, Witold; Zatoński, Mateusz (Journal of Health Inequalities, 2016)
Before World War II (WWII) Poland was one of the countries with the poorest health in Europe. In the 1930s life expectancy in Poland was around 46 years in both sexes; in the same period in Germany it was over 61 years. Infant mortality was estimated at the level of 150 deaths per 1000 live births. The situation was exacerbated by WWII; between 1939 and 1945 life expectancy in Poland fell by 20-25 years. The health transformation that took place in Poland after WWII proceeded very rapidly. Control of infectious diseases and infant mortality became a state priority in the post-war Polish People’s Republic. The epidemiological transition that in the United Kingdom or Germany took almost a century, in Poland, and many other Central and East European (CEE) countries, occurred in the two decades following WWII. This process led the CEE region to almost closing the health gap dividing it from Western Europe in the 1960s. Life expectancy in Poland increased to 70 years and infant mortality decreased to 30 deaths per 1000 live births. However, simultaneously, after WWII the seeds of the epidemic of man-made diseases were sown in CEE. In Poland the consumption of vodka and smoking prevalence reached some of the highest levels in Europe. This dramatic increase in exposure to lifestyle risk factors (an increase in cigarette sale from 20 billion cigarettes per annum after WWII to around 100 billion in the 1980s, and an increase of alcohol consumption from 3 litres per annum to nearly 9 litres in the same period), led Poland and the CEE region to a health catastrophe caused by the rise of chronic diseases. Diseases such as lung cancer, laryngeal and oral cavity cancers, cardiovascular diseases (e.g. ischaemic heart disease and stroke), sudden deaths from external causes (e.g. accidents, injuries, poisonings etc.), and liver cirrhosis, all reached in Poland some of the highest levels observed globally. In contrast to most Western democracies, authorities in communist states of CEE were unable to cope with these new health challenges, which demanded comprehensive, also non-medical solutions. Health literacy was low, also among the better educated segments of population, including the political class.